Solusi Deret Pangkat Tetap Dengan Fungsi Pembangkit - Gunawan, Alexander A.S. (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This article discusses about the sum of powers , which closed solutions empirically have been discovered by Jacob Bernoulli in 1731 in The Art of Conjecture. In this paper, we will find a closed solution of the sum of powers by using the Generating Function. By learning how to derive the closed solution of the sum of powers, the Generating Function can be used to solve the more general series forms.